2023
DOI: 10.1073/pnas.2200626120
|View full text |Cite
|
Sign up to set email alerts
|

Long-term persistence and functionality of adoptively transferred antigen-specific T cells with genetically ablated PD-1 expression

Abstract: Engagement of the inhibitory T cell receptor programmed cell death protein 1 (PD-1) associates with dysfunctional states of pathogen- or tumor-specific T cells. Accordingly, systemic antibody-mediated blockade of PD-1 has become a central target for immunotherapies but is also associated with severe toxicities due to loss of peripheral tolerance. Therefore, selective ablation of PD-1 expression on adoptively transferred T cells through direct genetic knockout (KO) is currently being explored as an alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…In a clinical trial with PD-1 disrupted cells edited for T cell specificity, the frequency of cells with edits in the PDCD1 locus decreased from 25% to 5% of the cells expressing the transgenic TCR at 4 months after infusion, consistently with mouse studies of chronic infection where PD-1 deficient T cells proved less able to establish memory ( 23 ). However, recent reports challenged this hypothesis and demonstrated in a murine model long-term persistence and function of murine adoptively transferred antigen-specific T cells with genetically ablated PD-1 expression ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical trial with PD-1 disrupted cells edited for T cell specificity, the frequency of cells with edits in the PDCD1 locus decreased from 25% to 5% of the cells expressing the transgenic TCR at 4 months after infusion, consistently with mouse studies of chronic infection where PD-1 deficient T cells proved less able to establish memory ( 23 ). However, recent reports challenged this hypothesis and demonstrated in a murine model long-term persistence and function of murine adoptively transferred antigen-specific T cells with genetically ablated PD-1 expression ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that blocking immune checkpoints has the potential to reactivate T cells, a key question of interest would be whether selective reduction or elimination of immune checkpoint genes on T cells effectively maintain or enhance CAR-T cell function? Research has proved that employing CRISPR/Cas9 to delete PD-1 resulted in enhanced long-term persistence and activity of CAR-T cells (preclinical study) ( 20 ), and similarly, the deletion of CTLA-4 using CRISPR/Cas9 improved the proliferation and activity of CAR-T cells (preclinical study) ( 21 ). Numerous investigations conducted thus far have demonstrated that the abrogation of immune checkpoint inhibition can effectively enhance and optimize the performance of CAR-T cells across various dimensions ( Table 2 ).…”
Section: Crispr/cas9 Technology and Pcar-t Cellsmentioning
confidence: 99%
“…In addition to the epigenetic modification, antitumor functions of CAR-T cells can be potentiated through ablation of various genes. For example, PDCD1 [ 52 , 53 ], CTLA4 [ 54 ], TGFBRII [ 55 ], and A2AR knockout [ 56 ] can block the suppressive signals from the tumor microenvironment and enhance effector functions of CAR-T cells.…”
Section: Introductionmentioning
confidence: 99%